Turkish guest workers in Germany hidden lives and contested borders, 1960s to 1980s - Miller, Jennifer A. 1976- (University of Toronto Press, 2018)
Turkish Guest Workers in Germany tells the post-war story of Turkish "guest workers," whom West German employers recruited to fill their depleted ranks. Jennifer A. Miller’s unique approach starts in the country of departure rather than the country of arrival and　is heavily informed by Turkish-language sources and perspectives. Miller argues that the guest worker program, far from creating a parallel society, involved constant interaction between foreign nationals and Germans. These categories were as fluid as the Cold War borders they crossed. Miller’s extensive use of archival research in Germany, Turkey and the Netherlands examines the recruitment　of workers, their travel, initial housing and work engagements, social lives, and involvement in labour and religious movements. She reveals how contrary to popular misconceptions, the West German government attempted to maintain a humane, foreign labour system and the workers themselves made crucial, often defiant, decisions. Turkish Guest Workers in Germany identifies the Turkish guest worker program as a postwar phenomenon that has much to tell us about the development of Muslim minorities in Europe and Turkey’s ever-evolving relationship with the European Union
Keywords: Geschichte 1960-1990; Foreign workers, Turkish -- Germany -- History -- 20th century; Turks -- Germany -- Economic conditions -- 20th century; Turks -- Germany -- Social conditions -- 20th century; Lebensbedingungen; Türkischer Arbeitnehmer; Arbeitsbedingungen; Deutschland